Rancangan media pembelajaran berbasis audio pada pembelajaran bahasa arab materi نُزْهَة kelas vi - 'Adhim, Rizka Maziyyah (Maliki Interdisciplinary Journal, 2025)
This study aims to design an audio-based learning media for Arabic subject, specifically on the topic Nuzhah for sixth-grade elementary/madrasah students. The research was motivated by the limited availability of Arabic learning media aligned with the Merdeka Curriculum, particularly in developing istima’ (listening) skills. The research employed the Research and Development (R&D) approach using the ADDIE model, limited to the Analysis, Design, and Development stages. Data were collected through observation, interviews, and documentation. The result of the development is a digital media called ABU NAWAS, packaged as an interactive audio book complemented by practice exercises using liveworksheet and wordwall. The media was designed to facilitate students in learning vocabulary, narratives, and Arabic structures through the discovery learning approach. The product remains at the design stage and has not yet undergone implementation or evaluation. Therefore, it holds potential to enhance students’ listening skills in a more engaging and contextual way, though further validation and testing are required.